(untitled) (Global Journal of Human-Social Science, 2024)
The text addresses the controversies about conceptions of development processes and locates the polarizations around the concepts of economic development and economic growth as well as social development and economic development and their most common qualifiers As an illustration of the theoretical discussion and link with the empirical reality is used the figure of the urban park Parque Popular da Pedreira located in the municipality of Iju in the northwest region of the State of Rio Grande do Sul From the argument emerges the mental figure of an iceberg invoked virtually as reality Figuratively although the Park can be characterized by its most visible end in this case the social aspect nevertheless this can not do without the non-visible and submerged part The economic aspect constitutes the true basis of the support of the whole set